The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnins.2019.00628
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Way for Studying Neural Basis of Basic Emotions With fMRI

Abstract: How emotions are represented in the nervous system is a crucial unsolved problem in the affective neuroscience. Many studies are striving to find the localization of basic emotions in the brain but failed. Thus, many psychologists suspect the specific neural loci for basic emotions, but instead, some proposed that there are specific neural structures for the core affects, such as arousal and hedonic value. The reason for this widespread difference might be that basic emotions used previously can be further div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 160 publications
3
53
0
Order By: Relevance
“…The regression results showed that life events had a significant positive effect on depression, and coping style had a significant negative predictive effect on depression. These findings are consistent with previous studies showing that individuals with negative coping style are more likely to have mood disorders such as anxiety and depression [ 31 ], highlighting the importance of coping styles established early in life.…”
Section: Discussionsupporting
confidence: 93%
“…The regression results showed that life events had a significant positive effect on depression, and coping style had a significant negative predictive effect on depression. These findings are consistent with previous studies showing that individuals with negative coping style are more likely to have mood disorders such as anxiety and depression [ 31 ], highlighting the importance of coping styles established early in life.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is no efficient treatment for this disease, for the underlying neural mechanism of emotions is unclear [2]. The most widely accepted theory about affective disorders is the monoamine theory, which suggests that monoamines, including norepinephrine, dopamine, and serotonin (5-HT) are the major reasons for emotion disorders [3], and the first line of treatment for depression also targets these monoamines [4]. However, there are still many controversies about monoamine neurotransmitters affecting the emotion processes, for example, it is well known that 5-HT is a major neurotransmitter that is involved in depression; and sleep is also modulated by 5-HT in raphe nuclei, but how sleep affects depression is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Although the compensatory plasticity hypothesis suggests that blindness associates with compensation for the loss of vision through more efficient use of the spared modalities [45], [65]. In this sense, provided that sadness is associated with more systematic and deliberate processing whereas happiness is associated with more heuristic processing, [66], [67] it is tempting to hypothesize that in the present study the blinds based on more heuristic adaptive processes and less systematic and deliberate processing.…”
Section: B Behavioral Performancementioning
confidence: 64%